2021
DOI: 10.1111/1756-185x.14219
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 polymorphisms in Thai patients with rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis

Abstract: Aims: Studies on polymorphisms of the cytotoxic T lymphocytes associated antigen-4 (CTLA-4) genes in rheumatic disease patients are limited in Southeast Asia. This pilot study aimed to determine CTLA-4 polymorphisms in Thai patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), and correlate them with serology. Method: One-hundred RA, 70 SLE and 50 SSc patients, and 99 healthy controls (HCs) were included in this study. Polymorphisms of the CTLA-4 gene at +49A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…The findings of this study suggest that SERPINA1 may be a tumor‐promoting factor in gastric cancer, which is in line with previous studies 2 . In addition, the authors used protein–protein interaction analysis to investigate the relationship between SERPINA1 and CTLA4, a protein that plays an important role in regulating the immune system 3 . We found that SERPINA1 and CTLA4 have crosstalk through the intermediate regulators PLG and ELANE proteins.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study suggest that SERPINA1 may be a tumor‐promoting factor in gastric cancer, which is in line with previous studies 2 . In addition, the authors used protein–protein interaction analysis to investigate the relationship between SERPINA1 and CTLA4, a protein that plays an important role in regulating the immune system 3 . We found that SERPINA1 and CTLA4 have crosstalk through the intermediate regulators PLG and ELANE proteins.…”
Section: Figuresupporting
confidence: 90%
“…2 In addition, the authors used proteinprotein interaction analysis to investigate the relationship between SERPINA1 and CTLA4, a protein that plays an important role in regulating the immune system. 3 We found that SERPINA1 and CTLA4 have crosstalk through the intermediate regulators PLG and ELANE proteins. Furthermore, the authors analyzed the relationship between SERPINA1 and CTLA4 using the TIMER immune database and found a strong positive correlation between the 2, as shown in Figure 2.…”
mentioning
confidence: 76%
“…Polymorphisms of multiple genes and molecules have been shown to be associated with SLE, such as the cytotoxic T lymphocyte associated antigen‐4 ( CTLA4 ) gene 29 and sirtuin‐1 ( SIRT1 ) 30 . The interleukin pathways have been commonly implicated in the development of SLE 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) within the CTLA-4 gene are most commonly asso-ciated with aetiopathogenesis of these diseases. An emerging variation in the DNA sequence involves the substitution of a single nucleotide for another nucleotide [7]. The CTLA-4 gene has many variants and polymorphic forms, among which the most commonly examined was +49A/G polymorphism.…”
Section: The Role Of Ctla-4 and Pdcd-1 Gene Polymorphisms In The Deve...mentioning
confidence: 99%
“…The CTLA-4 gene has many variants and polymorphic forms, among which the most commonly examined was +49A/G polymorphism. In a study by Louthrenoo et al [7], 100 RA patients, 50 SSc patients, 70 SLE patients and 99 healthy controls were analysed for CTLA-4 SNPs. It was found that out of the four CTLA-4 loci (+49A/G, -318C/T, -1661A/G and -1722T/C), the A allele polymorphism at the +49A/G locus was significantly more frequent in RA patients.…”
Section: The Role Of Ctla-4 and Pdcd-1 Gene Polymorphisms In The Deve...mentioning
confidence: 99%